Analisis Quality of Service Protokol MQTT, HTTP, dan CoAP dalam Pengiriman Data ke Thingsboard - Kurniawan, I Kadek Yogi; Andika, I Gede; Antara, I Gede Made Yudi; Desnanjaya, I Gusti Made Ngurah; Ekayana, Anak Agung Gde (Faculty of Computer Science, University of Jember, 2024)
The Internet of Things allows a sensor node to collect data from a place and send it to the Internet of Things platform. In its application, the Internet of Things has several protocols for sending data such as Message Queue Telemetry Transport (MQTT), Hyper Text Transport Protocol (HTTP), and Constrained Application Protocol (CoAP). These three protocols have their own characteristics and differences. For this reason, it is necessary to analyze the performance of these three protocols. This research focuses on analyzing the comparison of the Quality of Service of these three protocols in terms of packet loss, delay, and jitter parameters with the object used is sending temperature data to Thingsboard. The result shows that MQTT excels in sending data with short time intervals and CoAP excels in sending data with long time intervals.